Łzy Słowackiego. Rekonesans - Piechota, Marek (Śląskie Studia Polonistyczne, 2012)
When the historian of the Polish literature thinks of Romanticists’ tears, he momentarily remembers a „tear-poem” by Adam Mickiewicz , five verses on an incipit Polały się łzy me czyste, rzęsiste…, around which an extremely rich literature of the subject has been created. Yet, Słowacki has his own poem which should impose itself in this context and require interpretation. This is a lyrical miniature, an elusive fragment on the disillusion of words: Bo to jest wieszcza najjaśniejsza chwała… (the very poem has been interpreted only once within the studies conducted). On a closer look, it appears that the motif of tears is frequent in Słowacki’s works as he did not leave tears in his real biography be it at home or in his books for children and youth. A full realization of the project on Słowacki’s tears would make a thick book, while in this article just a reconnaissance.